Using the completing-the-square method, rewrite f(x) = x2 − 8x + 3 in vertex form.
f(x) = (x − 8)^2
f(x) = (x − 4)^2 − 13
f(x) = (x − 4)^2 + 3
f(x) = (x − 4)^2 + 16

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Then wouln't it be the second one?

:-)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.